Cryptanalyzing an image cipher using multiple chaos and DNA operations - Wen, Heping; Lin, Yiting (Journal of King Saud University. Computer and information sciences, 2023)
Recently, an improved color image cipher (ICIC-DNA) based on multiple deoxyribonucleic acid (DNA) sequence operations with DNA synthetic image and chaos was proposed. ICIC-DNA features the use of multiple chaotic systems and diverse DNA operations. However, after our careful cryptanalysis, we found that ICIC-DNA has several fatal security flaws. First, despite the use of multiple chaotic systems, the corresponding encryption sequences are independent of the plaintext, such that equivalent keys exist. Second, the diverse DNA operation is essentially a 2-bit data substitution process, and thus can be equivalently simplified. Third, ICIC-DNA includes substitution and permutation of DNA domains, and based on the equivalent simplification operation, the substitution and permutation can be attacked separately. Based on these, we propose a chosen-plaintext attack method to attack ICIC-DNA. Differential analysis is firstly adopted to break the DNA-base permutation process, and then the DNA domain encryption is eliminated, and finally the equivalent key is used to achieve complete cracking. Theoretical analysis and experimental results show that the proposed attack method is effective and has low computational complexity and data complexity.